Aconselhamento cristão e cidadania : desafios, reflexões e propostas na perspectiva dos nordestinos das periferias de São Paulo - Ferreira, Paula Coatti (2011)
This study focuses on the contribution of Christian counseling to develop social consciousness regarding the Northeastern Brazilian population living in the outskirts of the city of Sao Paulo. For that matter, this research is divided into three parts. The first part analyzes the socio-economic and religious profile of the Northeastern Brazilian population living in the outskirts of the city of Sao Paulo and the influences of their migratory origins and the main characteristics intrinsic to the formation and change of their cultural and personal identity. The second part outlines the type of Christian counseling that is currently offered and identifies applicable benchmarks to recover personal and cultural identity and provide these individuals with human integrity, and it also recognizes the most appropriate kind of counselor to develop such task. The third and last part evaluates the possible development of social consciousness regarding both the individual and the church, and it establishes limits and future perspectives for them. The final consideration highlights how important Christian counseling is in the development of social consciousness regarding the Northeastern Brazilian population living in the outskirts of the city of Sao Paulo by specifically using applicable benchmarks and what future consequences there will be for the Christian church in the current Brazilian social context.